Implementasi Penguatan Pendidikan Karakter (PPK) Berbasis Kelas Online (Daring) pada Masa Pandemi COVID-19 - Ristati Ristati; Shanty Savitri (LPPM Universitas Palangka Raya, 2022)
In the implementation of Curriculum 2013, especially in Elementary School, the more emphasis is placed on Penguatan Pendidikan Karakter (PPK) with the percentage of education of character reaching 80 percent and only 20 percent for the knowledge. Based on the Circular Number 4 of 2020 Issued by the Minister of Education and Culture on the implementation of education during the Covid-19 pandemic, the government took the anticipatory step that was implementing an online learning system across all levels of education. Teachers are required to be more creative in providing the learning materials and instilling the character education values to the students. Based on the results of the pre-survey, there were two problems: (1) The teachers had difficulty in integrating the main character education values, such as religiosity, nationalism, integrity, independence, and mutual cooperation into the lesson plan; (2) The teachers found it difficult to determine the right learning media for online classes. The solutions provided by the PKM team were by giving a training on how to integrate the character values into the lesson plan and how to create learning videos for online class. The resource people for the training were the team of lecturers and FKIP students from University of Palangka Raya. The training participants were all teachers at Sekolah Dasar Islam Terpadu (SDIT) Al Ghazali Palangka Raya. The results of this activity show that the teachers have succeeded in formulating RRP which has the integrated character values and implemented them in the learning process. In addition, they have also succeeded in designing the learning video and implementing them in the online learning.